REVIEW ARTICLE: HISTOPATHOLOGICAL CHANGES IN PLACENTA AND RELATIONSHIP WITH CORONAVIRUS INFECTION DURING PREGNANCY - Moheiseen Al-Taee , Rajaa Ali; Al-Taee , Amal Ali (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
During Covid-19 pandemic, Severe Acute Respiratory Syndrome - Coronavirus 2 (SARS-CoV-2) was significantly more severe in pregnant women than in non-pregnant women, leading in a number of health-related consequences that impacted healthcare, including fetal and maternal ramifications. Infection by coronavirus 2 can harm placental tissue by causing a variety of alterations. The majority of patients with SARS-CoV-2 are asymptomatic or have moderate symptoms related to upper respiratory infections that could sometimes escalate to severely sickness, injury of multi-organ, system failure, and death.Evidence about the effects of maternal infection is growing. Emerging information points to an increase in the dangers associated with obstetrics, such as stillbirth, gestational diabetes, maternal problems, preterm births, hypertensive disorder, reduced intrauterine fetal growth, and a chance of neonatal impairments of development. Generally, it remains contradictory concerns regarding the possibility of vertical transmission. Further analysis is needed on the placenta and its role in pregnancies with COVID-19 since impairment of placental function effects on fate of pregnancy. The reviewed studies referred to present of changes in the architecture of tissues as histopathological alterations accompanied coronavirus 2 outbreaks. The current review study can be a guide that helps doctors and researchers in the future to clarify effective plans in diagnosing and treating cases of this epidemic to prevent the risks it causes.